BIOKIMIA DI ERA BIG DATA GENOMIK: TANTANGAN, APLIKASI DAN PELUANG INOVASI - Saudale, Fredy Z. (Chemistry Notes, 2020)
The completion of human genome project at beginning of 21st century with the advancement of computer technology has transformed Biochemistry into a genomic era. Further, it is accelerated by parallel and massive genome sequencing technology known as next generation sequencing (NGS) that enhances the identification of genetic variants associated with complex diseases such as cancer, diabetes and Alzheimer. Currently, this knowledge has been driving the development of precision and personalized medicine. Wisely applied, it is believed that the explosion of genomic big data can be of great use in advancing the diagnosis, therapy and drug discovery to combat complex diseases.